Implementation Study of the National Library Regulation Number 2/2024 Regarding National Standards for Public Libraries at the Balaiyanpus DPAD DIY - Ramadhan, Ndaru; Centia, Selvi; Setiawati; Harta, Ridho (Buletin Perpustakaan, 2025)
Ensuring that library services strictly comply with national library standards is urgently essential. As a government institution responsible for managing library affairs, the Balaiyanpus DPAD DIY must deliver high-quality and fully standardized public services without compromise. Failure to meet these standards can directly undermine service effectiveness, whereas strong adherence will significantly enhance service performance and boost public satisfaction.. The descriptive and qualitative research method is implemented by systematically collecting data through literature reviews, direct observations, and documentation analysis. National Library Regulation No. 2/2024 serves as the main reference to operationalize a legalistic analysis, which is then compared with the empirical conditions observed in the field. Nine aspects with 18 success indicators are examined through a legalistic analytical approach. The findings urgently demonstrate that the Balaiyanpus DPAD DIY has complied with the national standards for provincial library services as mandated by National Library Regulation No. 2/2024. Given the critical role of standardization in ensuring accountable and high-quality public services, future research should promptly extend this analysis to encompass the full scope of national standards for provincial libraries stipulated in the regulation.